Neuroprotective Effect of Ketone Metabolism on Inhibiting Inflammatory Response by Regulating Macrophage Polarization After Acute Cervical Spinal Cord Injury in Rats - Lin, Junyu; Huang, Zucheng; Liu, Junhao; Huang, Zhiping; Liu, Yapu; Liu, Qi; Yang, Zhou; Li, Ruoyao; Wu, Xiuhua; Shi, Zhe; Zhu, Qingan; Wu, Xiaoliang (Frontiers in Neuroscience, 2020)
Objective: To investigate the effects of ketogenic metabolism on macrophage polarization, inflammation inhibition and function recovery after acute spinal cord injury in rats. Methods: Sixty-four adult male Sprague-Dawley rats were randomly and equally divided into sham, standard diet (SD), ketone diet (KD) and 1, 3-butanediol (BD) groups. All animals underwent C5 unilateral laminectomy, while the SD, KD and BD groups underwent C5 spinal cord hemi-contusion. The impact rod with a diameter of 1.5 mm was aligned 22.5° to the left and 1.4 mm to the midline, and then triggered to deliver a set displacement of 1.5 mm at a speed of 100 mm/s. The gene expression of inflammatory factors, as well as the protein expression of inducible nitric oxide synthase (iNOS), arginase-1 and inflammatory factors were measured at one week post-injury. Serum ketone and behavior were evaluated every second week for 12 weeks. Then, histological analyses of the gray and white matter at the epicenter were conducted at 12 weeks post-injury. Results: The serum ketone levels of the KD and BD groups were significantly increased when compared with the SD group. The gene and protein expression of TNF-α and IL-1β tended to increase after the spinal cord injury, but were inhibited in the KD and BD groups. The protein expression of iNOS, marker of M1 macrophage, was inhibited in the KD and BD groups; while the expression of arginase-1, marker of M2 macrophage, was boosted in the KD and BD groups. The usage of the ipsilateral forelimb was higher in the KD group than in the SD group. The hemi-contusive injury resulted in an obvious ipsilateral lesion area at the epicenter, and there was no significant difference between groups regarding the lesion size. However, the spared gray matter area was significant greater in the KD group than in SD and BD groups. Conclusion: The present study suggests that ketogenic metabolism promotes macrophage polarization to M2, inhibits an inflammatory response and alleviates the loss of gray matter after spinal cord injury. A higher ketone level, such as induced by the ketogenic diet, seems to benefit function recovery following spinal cord injury.